Studying the effects of space in patient experience using multisensory perceptions a grounded theory approach on selected emergency rooms in Metro Manila - Perez, Maria Victoria F. (College of Architecture, University of the Philippines Diliman, 2019)
Patient experience is on of the few ways that healthcare consumers distinguish the difference of healthcare providers. ER being the entrance gateway of hospital admission represents the initial impression of patients and is a good opportunity to establish the "First impression" to the health-care provider. What is the role of space in the patient's experience in an ER setting? The purpose of this study is to answer this research question through intensive inquiry and analysis of the experience of 26 ambulatory ER patients, pre-selected to present varied ambulatory medical conditions. These participants were asked to narrate their patient experience in an ER setting using the multi-sensory perceptions or the seven senses: visual, auditory, olfactory, gustatory or taste, touch or somatosensory, vestibular system and proprioception. Open-ended interviews were used to gain the patient experience of each of the participants from their arrival and admission to ER, the clinical processes performed on them, to their discharge and departure from ER. The grounded theory method developed by Glaser and Strauss was the methodology used to collect, investigate and interpret the patient's descriptions. Constructed on the participant's account of experiences, each data was coded, word for word, line by line to develop and generate theories. Based on the narratives of patients, the study conceptualizes various aspects of patient experiences that contributed to how they perceived patient centered care. Three core categories were developed under this study: space perception, user experience and client satisfaction and outcome. These were brought together to form theories of patient experience in ER setting. These theories were validated through triangulation method by intensive interview of five ER medical practitioners and document review. A new model of designing an ER is presented as the Star Framework. This framework highlights two core concepts: branding and experiential space, and six sub-concepts: identity, color psychology, scent marketing, semiotics, proxemics and psychology of waiting. The implications were discussed in the content of the presently changing healthcare system in the country.